Integrating ALN into an Independent Study Distance Education Program: NVCC Case Studies - John Sener; Mary Liana Stover (Online Learning, 2019)
This paper describes eight ALN courses developed under various Sloan Foundation-funded degree program initiatives at Northern Virginia Community College (NVCC) Extended Learning Institute (ELI). These chemistry, engineering, mathematics, and information technology courses offer useful lessons about what makes ALN courses successful. The courses incorporated ALN into an independent study format to increase interaction among learning participants while maximizing learner convenience and flexibility; some courses also focused on both online and in-person collaboration. A wide variety of other course design and delivery strategies contributed to the courses' success. The results of this study indicate that ALN courses can be viable and successful for community college students and that ALN can succeed in a distance education program delivered in an independent study format to motivated learners. NVCC/ELI's experience also suggests that ALN works within a multiple media approach to course design and delivery; that faculty selection, support, and development are critical factors in assuring quality ALN courses; that a wide variety of best practices can result in successful ALN courses; and that the learning effectiveness of ALN courses will continue to improve as better tools, content, and support are developed.